Assessing basketball offensive structure: The role of concatenations in space creation dynamics - Santana, F.; Fellingham, G.; Rangel, W.; Ugrinowitsch, C.; Lamas, L. (International Journal of Sports Science & Coaching, 2019)
The aims of the present study were to systematize a set of concatenated space creation dynamics in basketball and to use it to analyze teams` offenses. Space creation dynamics concatenation concept was investigated and classes were defined. Modeling resulted in independent and dependent concatenations` classes. Agreement was at least 0.85 for all space creation dynamics classes. Afterwards, space creation dynamics classes were applied to match analysis. Analytic procedures encompassed both the frequency and types of space creation dynamics in ball possessions. The four best teams on the 2013-2014 NBA season were evaluated. The Thunder had more ball possessions with a single space creation dynamics than expected, while the Spurs had longer sequences than expected with four or more dependent concatenations. Interestingly, the Heat and the Thunder had the highest number of dependent concatenated space creation dynamics two steps ahead of the outcome. Additionally, the Heat was the team with greatest diversity of space creation dynamics and the highest frequency of dependent concatenations one step before the outcome. Results indicated that the analytical framework efficiently discriminated teams` strategies. The concatenation concept helped elucidating how teams approach defensive disruption, with more straight or progressive space creation and concatenated space creation dynamics performed one or two steps before the outcome.